К палеоантропологии средневекового населения Поволжья - Яблонский, Л.Т. (Степи Европы в эпоху средневековья, 2008)
Physical appearance of the population of the Golden Horde resulted from interbreeding of representatives of two big races, i.e. the Mongoloid and the Caucasoid. The presence of the Mongoloid component is to some extent manifested in the appearance of inhabitants of all the Golden Horde towns. Nevertheless, it is the Caucasoid features that prevailed in urban population.